Everyone at the table : engaging teachers in evaluation reform - Behrstock-Sherratt, Ellen (Jossey-Bass, A Wiley Brand, 2013)
A proven method for working with teachers to design better evaluations There is no magic formula for successfully designing a teacher evaluation system. However there is abundant evidence that suggests involving teachers in the process will reduce the likelihood of opposition, gridlock, and reform failure. Everyone at the Table provides materials to genuinely engage teachers in the evaluation process. The book is a research-based and field-tested practical guide for school leaders. With this resource, educators will have the tools they need to develop meaningful teacher evaluat.